(untitled) (Editora Impacto Científico, 2025)
Assistive Technology is an area of knowledge, with an interdisciplinary characteristic, which connect products and resources that reasons to promote activity and participation of people with disabilities, aiming at their autonomy and quality of life. The orthostatic bed is a device it goals to ensure an aligned and comfortable posture to the patient. Orthostatism consists of changing the patient’s horizontal position to angled positions from 0º to 90º. It takes seven days of bed rest for muscle strength to decrease by 30%, with an additional 20% loss of strength remaining each week. Therefore, with the use of the orthostatic bed, information is sent to the nervous system, where the body is biomechanically aligned, stretching and strengthening muscle groups, avoiding deformities in the lower limbs and providing functionality for the upper limbs. The present article is based on the modeling, sizing and simulation of a new prototype of orthostatic bed based on existing models, but with essential design changes, in addition to performing kinematic analyzes in lifting mechanisms and performing mechanical simulations by beam elements in the structure. The research was elaborated in order through the discussion of the main aspects that should be considered in the project, especially for occupational therapists and professionals who work directly with assistive technology. The simulation results indicate that the modeled structure reaches the design objectives and resists the efforts from the requested load, the result of an alternative device with a lower cost compared to the market, easy assembly and maintenance.